Numerical simulation of reflux swirling nozzles for desulfurization tower - Shengqian Kuang; Xiang Wang; Runyang Zhang; Qitao Lin; Ganyong Wu; Yilong Rao; Jianchun Wang; Wenwang Li (AIP Advances)
This study presents an investigation of reflux swirling atomizing nozzles employed in industrial desulfurization towers to enhance operational efficiency. Computational fluid dynamics simulations, incorporating the volume of fluid model coupled with the RNG k–ε turbulence model, were conducted to analyze the complex internal flow characteristics. Experimental validation was conducted to confirm the feasibility and accuracy of the numerical simulation model, with the simulation errors of atomization angle within 10% compared to experimental data. The simulation results revealed that the internal flow field of the reflux swirling nozzle exhibits complex flow phenomena, including the formation of vortices in the swirl chamber and the generation of an air core. The pressure and velocity variations in the nozzle were also investigated. The reflux outlet pressure and backflow volume fraction have substantial effects on the velocity of flow field at the nozzle outlet and the atomization performance. This study may provide valuable insights into the optimization of reflux swirling nozzle operation and the enhancement of desulfurization efficiency in practical industrial applications.